A Descriptive Study of English Morphemes in terms of Inflectional and Derivational Suffixes in Journal Articles of JDER 2023 - Aziiz Rahman Putra; Ami Pradana (English Education Study Program Faculty of Teacher Training and Education, 2024)
This research is concerned with the morphological analysis of inflectional and derivational suffixes used in Journal Articles of JDER 2023 on Volume 4 No 3 (2023). In line with the research objectives are to describe the types of inflectional and derivational suffixes found in Journal Articles of JDER 2023; and to find out the most dominant types of inflectional and derivational suffixes appeared in Journal Articles of JDER 2023. This research is carries out in both methods, firstly quantitative and secondly qualitative. The sample of this research was all Journal Articles of JDER 2023 on Vol 4 No 3 (2023). The data were gathered by using checklist on data sheet based on Fromkin’s theory (2003) which states that inflectional suffixes are divided into eight types and derivational suffixes are divided into nine types and were analysed by using descriptive technique. The findings showed that all types of inflectional suffixes are found in Journal Articles of JDER 2023 with the most dominant types appeared are types of inflectional suffixes in ‘plural’ indicators namely suffixes (-s/-es plural) which occur 145 times with 114 in regular inflection and 31 suppletive forms as types of inflectional suffixes in irregular inflection. On the contrary, not all types of derivational suffixes found in Journal Articles of JDER 2023 with the most dominant types appeared are types of derivational suffixes in ‘verb to noun’ indicators (nominal suffixes) namely suffixes (-al, -ance, -ion, -ance, -ence, -ing) Noun which occur 70 times.